OCCUPATIONAL NOISE EXPOSURE ANALYSIS IN THE FOOD INDUSTRY - Spear, Brenda; Rodolpho , Daniela (Revista Interface Tecnológica, 2022)
Hearing loss caused by exposure to high levels of noise in the workplace is still one of the greatest risks to workers, as most do not notice the difference and over time it ends up impacting their quality of life. Hearing loss can slowly worsen, bringing several problems that can lead to hearing loss or even become irreversible. The main objective of the present quantitative study was to analyze the noise levels in a food industry located in the interior of the state of São Paulo, verifying if it would be in accordance with the limits established by the regulatory standard NR-15. In addition, it was possible to verify through questionnaires to the workers what types of hearing protection they used and if they had tinnitus in the ear or if they could hear well. The procedure for the analysis consisted of measuring the decibel levels through the decibel meter equipment. According to the results obtained, it was possible to observe that in the place there is the existence of continuous or intermittent noise levels. All sector employees were asked to prepare the survey results, requiring a more structured assessment to verify the problem. After the end of the analysis, a brief lecture to workers was suggested to the industry on the importance of hearing prevention for greater awareness.
Keywords: analysis; noise; prevention